Adsorption of zinc from aqueous solution using chemically treated newspaper pulp - Chakravarty, S.; Bhattacharjee, S.; Gupta, K. K.; Singh, M.; Chaturvedi, Hema T.; Maity, S. (Bioresource Technology, 2007)
Adsorption of zinc was studied using chemically modified newspaper pull) as an adsorbent in the aqueous medium. Quantitative chemical analysis showed the presence of trace quantities of some inorganic elements along with phosphorous in TNP. The experimental adsorption data fitted reasonably well to both Freundlich and Langmuir isotherm. pHzpc of TNP was 5.1, which indicated that the adsorbent was more potential for cationic adsorption. The adsorption kinetic data followed a pseudo-second order model for zinc. Optimum Zn2+ loading was 9.20 mg/g for 10.31 mg/l initial zinc concentration at pH 5.80. Zn2+ loading on TNP was dependent on initial zinc concentration. TNP was a potential adsorbent for the removal of Zn from the effluent of electroplating industry. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: Adsorption; newspaper pulp; TNP; zinc